Ezetimibe Improves Rosuvastatin Effects on Inflammation and Vascular Endothelial Function in Acute Coronary Syndrome Patients Undergoing PCI. (8th September 2021) - Sun, Changqing; Zheng, Wuyang; Liang, Ling; Liu, Zuheng; Sun, Wenchao; Tang, Rong
Abstract : Background . Little is known of the acute effects of ezetimibe in patients with acute coronary syndrome (ACS) undergoing PCI. We investigated whether ezetimibe improves inflammation and vascular endothelial function in patients with ACS undergoing PCI. Methods . We randomized 171 patients with ACS undergoing PCI to receive ezetimibe 10 mg/day plus rosuvastatin 20 mg/day (combination group, n  = 81) versus rosuvastatin 20 mg/day (rosuvastatin group, n  = 90). Lipid profile, type II secretory phospholipase A2 (sPLA2-IIa), interleukin-1 β (IL-1 β ), vascular cell adhesion molecule-1 (VCAM-1), and intercellular cell adhesion molecule-1 (ICAM-1) were measured at baseline and after 7 days. Three months after PCI, clinical outcomes were examined. Result . The levels of sPLA2-IIa and IL-1 β reduced significantly in both groups, but more when ezetimibe and rosuvastatin were coadministered (sPLA2-IIa: 6.16 ± 2.67 vs. 7.42 ± 3.53 ng/ml, p = 0.01 ; IL-1 β : 37.39 ± 26.25 vs. 48.98 ± 32.26 pg/ml, p = 0.01 ). A significant rise of VCAM-1 and ICAM-1 was observed on day 7 after PCI in the both groups, but was less in the combination group (VCAM-1: 918.28 ± 235.31 vs. 988.54 ± 194.41 ng/ml, p = 0.03 ; ICAM-1: 213.01 ± 100.15 vs. 246.88 ± 105.71 ng/ml, p = 0.03 ). Patients in the combination versus rosuvastatin group appeared to suffer from less major adverse events. Periprocedural therapy of ezetimibe improves rosuvastatin effects on proinflammatory responses and endothelial function associated with ACS patients undergoing PCI. This trial is registered with https://clinicaltrials.gov/ct2/show/ChiCTR-IPR-17012219 (Chinese Clinical Trial Registry, http://www.chictr.org.cn on 02/08/2017).